Genetic Mechanism of Geothermal Anomaly in the Gaoyang Uplift of the Jizhong Depression - Miao, Qingzhuang; Wang, Guiling; Qi, Shihua; Xing, Linxiao; Xin, Hailiang; Zhou, Xiaoni (Frontiers in Earth Science, 2022)
Gaoyang uplift is rich in geothermal resources, but there are few studies on the regional geothermal genetic mechanism.A large number of geothermal wells fail in position calculation because of shortage of basis. By using the methods of P-wave velocity structure imaging and magnetotelluric sounding, it draws the following conclusions: 1.The crustal thickness in Gaoyang uplift area is relatively thin, about 32km; 2.The cutting depth of Gaoyang East fault exceeds 28km and has reached the bottom of the lower crust. It is a large tensile fault, which provides the channel for mantle heat flow into the shallow crust; 3. Gaoyang uplift and its surrounding depressions form a concave convex base fluctuation mode, which is conducive to the accumulation of heat flow to the uplift; 4. The deep carbonate thermal reservoir in Gaoyang uplift is overlaid with Cenozoic sand and mudstone strata, with a thickness of more than 3000m and low thermal conductivity, which is conducive to the preservation of thermal storage heat. Therefore, the shortening of heat conduction path caused by regional crustal thinning, convective heat conduction of large faults, concave convex structure and thick Cenozoic caprock are the reasons why the heat reservoir temperature in Gaoyang uplift is higher than that around, which provides a theoretical basis for geothermal development and utilization.